Morphofunctional characterization of decellularized vena cava as tissue engineering scaffolds - Bertanha, Matheus [UNESP] (2014)
Clinical experience for peripheral arterial disease treatment shows poor results when synthetic grafts are used to approach infrapopliteal arterial segments. However, tissue engineering may be an option to yield surrogate biocompatible neovessels. Thus, biological decellularized scaffolds could provide natural tissue architecture to use in tissue engineering, when the absence of ideal autologous veins reduces surgical options. The goal of this study was to evaluate different chemical induced decellularization protocols of the inferior vena cava of rabbits. They were decellularized with Triton X100 (TX100), sodium dodecyl sulfate (SDS) or sodium deoxycholate (DS). Afterwards, we assessed the remaining extracellular matrix (ECM) integrity, residual toxicity and the biomechanical resistance of the scaffolds. Our results showed that TX100 was not effective to remove the cells, while protocols using SDS 1% for 2 h and DS 2% for 1 h, efficiently removed the cells and were better characterized. These scaffolds preserved the original organization of ECM. In addition, the residual toxicity assessment did not reveal statistically significant changes while decellularized scaffolds retained the equivalent biomechanical properties when compared with the control. Our results concluded that protocols using SDS and DS were effective at obtaining decellularized scaffolds, which may be useful for blood vessel tissue engineering. (C) 2014 Published by Elsevier Inc.